(untitled) (Biological Sciences - PJSIR, 2001)
Economic gain from sunflower-mungbean intercropping systems was assessed at University of Arid Agriculture, Rawalpindi, Pakistan, during spring and summer, 1996. Land equivalent values showed a significant advantage of intercropping in both the systems and the seasons. Economic analysis showed that sunflower + mungbean (I: I) during spring season and sunflower + mungbean (I :2) during summer season provided higher benefit cost ratio (BeR) and net income.